Stroke recurrence is associated with unfavorable intracranial venous outflow in patients with symptomatic intracranial atherosclerotic large vessel severe stenosis or occlusion - Gao, Jiali; Zhang, Liang; Lin, Jiaxin; Yang, Jiajie; Yao, Mingzheng; Cheng, Zhongyuan; Cai, Xiangran; Huang, Li’an (Frontiers in Neurology, 2023)
Objective: The purpose of this study was to investigate the predictive value of intracranial venous outflow for recurrent cerebral ischemic events (RCIE) in patients with symptomatic intracranial atherosclerotic large-vessel severe stenosis or occlusion (sICAS-S/O). Methods: This retrospective study included sICAS-S/O patients with anterior circulation who underwent dynamic computed tomography angiography (dCTA) and computed tomography perfusion (CTP). Arterial collaterals were evaluated using the pial arterial filling score for dCTA data, tissue-level collaterals (TLC) were assessed using the high-perfusion intensity ratio (HIR, Tmax >10 s/Tmax >6 s), and cortical veins were evaluated using the multi-phase venous score (MVS) for the vein of Labbé (VOL), sphenoparietal sinus (SPS), and superficial cerebral middle vein (SCMV). The relationships between multi-phase venous outflow (mVO), TLC, and 1-year RCIE were analyzed. Results: Ninety-nine patients were included, 37 of whom had unfavorable mVO (mVO-) and 62 of whom had favorable mVO (mVO+). Compared with the mVO+ patients, mVO- patients had a higher admission National Institutes of Health Stroke Scale (NIHSS) score (median, 4 [interquartile range (IQR), 0–9] versus 1 [IQR, 0–4]; P=0.048), larger ischemic volume (median, 74.3 [IQR, 10.1–177.9] versus 20.9 [IQR, 5–86.4] mL; P=0.042), and worse tissue perfusion (median, 0.04 [IQR, 0–0.17] versus 0 [IQR, 0–0.03]; P=0.007). Multivariate regression analysis showed that mVO- was an independent predictor of 1-year RCIE. Conclusions: For patients with sICAS-S/O of the anterior circulation, unfavorable intracranial venous outflow is a potential imaging indicator for predicting higher 1-year RCIE risk.